Simple Synthesis of CeO2 Nanoparticle Composites In Situ Grown on Carbon Nanotubes for Phenol Detection - Hu, Chao; Huang, Haiping; Yan, Yu; Hu, Yongmei; Liu, Sui-Jun; Wen, He-Rui (Frontiers in Chemistry, 2022)
via simple hydrothermal method, CeO2 was in-situ grown onto the CNTs to form CeO2/CNTs nanocomposites were synthesized with cerium nitrate as Ce resource. The morphology and structure were characterized by transmission electron microscopy and X-ray diffraction. The characterizations reveal that CeO2 nanoparticles are uniformly dispersed onto the surface of the pre-acidified CNTs. The electrochemical property of the synthesized nanocomposite was investigated in 0.1 M KCl electrolyte containing 2 mM [Fe(CN)6]3-/4-. The nanocomposites were employed to fabricate electrochemical sensor for phenol detection. The linear range for phenol detection measured by the differential pulse voltammetry method is 1–500 μM. The sensor also exhibits good selectivity, reproducibility and stability. When applied for the river and tap water analysis, it shows good recovery rate.